THE EFFECT OF SCRAMBLE MODEL ON STUDENTS’ VOCABULARY MASTERY - Lollo Rosa Lubis (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract : The purpose of this research to know 1) the application of the scramble model in vocabulary mastery 2) the students’ vocabulary mastery before and after using scramble model 3) whether there is any significant effect of scramble model in vocabulary mastery at the eleventh grade students of MA Swasta Al-Abraar Siondop Julu Angkola Selatan by applying pre-experimental (one-group pretest and posttest design). The sample consist of 22 students and they were taken by using purposive sampling technique. In collecting the data, the researcher used questionnaire and test. The result of the research are 1) application of scramble model was 93% (very good category), 2) the mean score of students’ vocabulary mastery before using scramble model was 58.86 (bad category) and after using scramble model was 80 (good category), 3) Data on students' vocabulary mastery analyzed using paired sample ttest and N- gain through SPSS 22. The pair sample ttest shows the significant value was 0.000, it’s less than 0.05 (0.000< 0.05). Furthermore N- gain shows 0.51. It means there is any significant effect of scramble model on students’ vocabulary mastery in medium category. Keywords: Vocabulary mastery, scramble model